School tours and philanthropy in Zimbabwe - Kathleen Smithers (Annals of Tourism Research Empirical Insights, 2024)
In Zimbabwe, partnerships with tourism companies enable schools to raise funds for infrastructure in exchange for allowing tourists to enter their school. This paper reports on one school using semi-structured interviews with teachers, school staff and tourism personnel. To shed light on the school tour, it explores three configurations of tours and funding. This paper argues that little is known about this type of tourism and by exploring three configurations of the school tour, it highlights the issues concerned with these types of partnerships and contributes a deeper understanding of these partnerships to the research literature.
Keywords: 330; Developmentourism; Philanthropy; Public-private partnerships; School tour; Zimbabwe